Fertility changes of soil under different uses in region of Brasnorte – MT - Vieira, Cristiane Ramos; Araujo, João Lucas da Silva; Weber, Oscarlina Lúcia dos Santos; Scaramuzza, José Fernando (Revista Ecologia e Nutrição Florestal - ENFLO, 2017)
The substitution of natural vegetation causes changes on the chemical properties of soil, in order to improve or degrade them. This study aimed to evaluate the changes in chemical of soil properties under different vegetation cover, with as a reference the Secondary Forest, Cerrado. The study was conducted in the municipality of Brasnorte - MT, considering the following systems: Secondary Forest (FS); Teak cultivation (Tectona grandis) of 19, sixteen years, thirteen years, and eight years; and pasture (PA). The experimental design was randomized blocks in factorial scheme, with soil samples collected at three depths (0 - 5, 5 - 10 and 10 - 20 cm) and subsequently analyzed chemical and physically. The removal of native vegetation to Teak cultivation and Pasture changed the chemical soil properties. The soil under Secondary Forest showed the highest levels of Ca²+, K+ and P, sum of base values, cation exchange capacity and cation saturation in the 0 - 5 cm depth. The soil under the pasture and Teak cultivation with 13 years had the highest TOC in the 0 - 5 cm depth, due to the organic matter formed in both cases.